Wireless Technologies for Wearable Electronics: A Review - Choong Yeon Kim; Juhyun Lee; Eun Young Jeong; Yeji Jang; Heesoo Kim; Bohyung Choi; Donggi Han; Youngjun Oh; Jae‐Woong Jeong (Advanced Electronic Materials, 2025)
Abstract Wireless technologies have profoundly transformed wearable electronics, advancing them from early, wired designs to untethered devices that seamlessly integrate into daily life. The adoption of wireless solutions has unlocked new possibilities, allowing for real‐time remote monitoring, enhanced comfort, and greater versatility across diverse settings. These advancements expand the applications of wearable electronics from activity tracking and health monitoring to rehabilitation, human–machine interfaces, and immersive virtual and augmented reality. However, the shift to wireless wearable electronics introduces unique challenges. Unlike traditional tethered systems, wireless wearable electronics must carefully balance power efficiency, communication stability, and user convenience without relying on wired connections. This review examines the recent advancements and challenges in implementing wireless wearable electronics, with a focus on wireless communication and power solutions. It begins by discussing key design considerations for achieving reliable wireless functionality in wearable electronics. Subsequently, it explores wireless communication technologies, ranging from short‐range protocols to long‐range networks, as well as powering methods, including integrated power sources and energy harvesting technologies. Their diverse applications, particularly in healthcare and interactive systems, are also discussed. Finally, the review highlights major challenges and outlines potential future directions to drive the development of the next generation of wireless wearable electronics.